The range of motion of the back squat exercise affects absolute volume load without changing the rating of perceived exertion - Josinaldo Jarbas da Silva; Willy Andrade Gomes; Silvio Luiz Pecoraro; Enrico Gori Soares; Roberto Aparecido Magalhães; Gustavo Zorzi Fioravanti; Rodrigo Baladán; Charles Ricardo Lopes; Paulo Henrique Marchetti (Universidade Federal de Santa Catarina, 2020)
The range of motion (ROM) may affect the external maximal load during back squat (BS) exercise. The correct ROM manipulation can be useful as an exercise load manipulation strategy, changing the volume load during a resistance training session. The aim of this study was to evaluate the acute effects of ROM on relative load, absolute load and the rating of perceived exertion (RPE) during partial and full BS exercise with adjusted loads. Fifteen male individuals (age: 26.5±4.5 years; height: 173±6 cm; body mass: 80.6 ± 8.8 kg; resistance training experience 5±3 years) participated in this study. The experimental procedure was conducted in two sessions. In the first session, brief familiarization and a 10-repetition maximal test (10-RM) was performed for partial (PBS) and full BS exercise (FBS) with 30-min of rest interval. During the second session, all subjects performed 1 set of 10-RM in both conditions (partial and full ROM), and relative load, absolute load, and RPE were evaluated. A paired t-test was used to compare means. The results showed higher values for PBS when compared to FE exercise: relative load (PBS: 1.14±0.24xBW vs. FBS: 0.87±0.24xBW; P<0.001), and absolute load (PBS: 925±249 kg x FBS: 708±232 kg, P<0.001). Similar RPE was observed between conditions (PBS: 8.6±1.3 IEP x FBS: 8.5±1.0 IEP, P=0.855). It was concluded that PBS allowed higher relative load and absolute load during 10RM, without effects on RPE.